Effect of stamping parameters of the spring-back behaviour of oil palm fibre composite - Che Mahzan, Muhammad ‘Ammar (2015)
Composite materials have been vastly known worldwide for its uses in various sectors such as aerospace, infrastructures and automotive industries. Natural fibres are gaining recognition as a substitute to synthetic fibres due to their recyclability and abundance. In Malaysia, research on palm fibre composite had mainly focused on tensile and flexural properties but not on its stamp forming behaviour. Oil palm fibre reinforced polypropylene composite panel has the potential to be stamp formed in order to build complex geometries. In stamp forming the most sensitive feature is elastic recovery during unloading. This phenomenon will affect the net dimension of the final product. This research studies the effects of tool radius, feed rate, temperature and weight ratio of fibre to polypropylene on the spring-back of oil palm fibre composite and to formulate an empirical equation to predict the spring-back angle. The composite material are mixed together with different fibre composition of 10wt%, 20wt%, 30wt%, 40wt% and pure polypropylene using an internal mixer and hot pressing. The samples are cut into rectangular shape samples with a dimension of 180mm x 20mm x 2mm for V-bend testing and are 160mm x 20mm x 2mm accooding to ASTM D3039 for tensile testing. A V-bending die is used to characterise the spring-back angle of the oil palm fibre composite. The results are computed using a statistical software (Minitab). Statistical analysis conducted shows all the studied parameters gave significant effect towards spring-back. Based on the analysed result, an empirical model was formulated to predict the spring-back angle. A stereo microscope was used as a visual aid to show the surface on the deformed area. It can be concluded that the higher the temperature, feed rate and fibre composition (up to 30wt %) the smaller the spring-back but the smaller the tool radius, the smaller the spring-back angle.